2000
DOI: 10.1002/1097-0142(20000715)89:2<424::aid-cncr30>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and postoperative factors affecting length of hospital stay after radical prostatectomy

Abstract: BACKGROUND Radical prostatectomy continues to comprise the mainstay of therapy for localized prostate carcinoma. However, caring for radical prostatectomy patients accounts for approximately half of the $1.7 billion annual cost of prostate carcinoma treatment. Length of stay (LOS) after surgery appears to be one of the main components of this cost. The first step in reducing cost is to identify those variables associated with LOS. Radical prostatectomy can be performed using two very different surgical techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 32 publications
1
23
0
2
Order By: Relevance
“…Medical expenditures for prostate cancer treatment in the U.S. totaled $1.3 billion in 2000, nearly 30% more than in 1994[38]. Furthermore, RP accounts for approximately half of all prostate cancer expenditures[39]. Given the large number of men with prostate cancer, the effects of treatment have major public health implications, including patient counseling and financial costs.…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
“…Medical expenditures for prostate cancer treatment in the U.S. totaled $1.3 billion in 2000, nearly 30% more than in 1994[38]. Furthermore, RP accounts for approximately half of all prostate cancer expenditures[39]. Given the large number of men with prostate cancer, the effects of treatment have major public health implications, including patient counseling and financial costs.…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
“…Gardner et al. [21] retrospectively assessed 114 and 197 patients who had PRP and RRP, respectively, and found that the mean time of food intake of the former was 24 h, vs 72 h for the latter group. In another study [11], the authors assessed the time to regular oral feeding, where the mean period was 2.3 days after PRP vs 5.1 days after RRP.…”
Section: Discussionmentioning
confidence: 99%
“…Our overall perioperative complication rate was quite low (0.66% for major complications and 6.6% for minor complications), and is comparable to that published by other high-volume centers. [12][13][14] Paralytic ileus was responsible for 45% of the complication-related increases in LOS. In an attempt to address this occurrence, we limited the amount of intravenous narcotics used by each patient by discontinuing the routine postoperative use of PCA machines and making intravenous pain medications available on an as-needed basis.…”
Section: Discussionmentioning
confidence: 99%